Occlusal plane canting: a treatment alternative using skeletal anchorage - Marcel Marchiori Farret
ABSTRACT A canted occlusal plane is the cause of unaesthetic smile, and also represents a challenge, due to the complex orthodontic procedures involved in its treatment. The skeletal anchorage allows successful treatment of this asymmetry in the majority of cases, with less dependency on the patient cooperation and reducing the necessity of orthognatic surgery. Given this condition, this article aims at discussing the main aspects related to the diagnosis of occlusal plane canting, treatment plan, and orthodontic mechanics using skeletal anchorage either by mini-implants or miniplates. In this context, five cases will be reported, showing the main details related to the orthodontic mechanics used to correct the occlusal plane, avoiding side effects and successfully reaching treatment objectives and long-term stability.